Respons Kacang Hijau (Vigna radiata L.) Akibat Takaran Pupuk Kandang Dan Frekuensi Penyemprotan KSM - Alima Maolidea Suri; Maryati Maryati; Windu Mangiring; Fizzaria Khasbullah (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Pertanian Dharma Wacana, 2022)
Mungbean are one of the food crops that produce 22% vegetable protein sources. It’s the third food crop after soybean and peanut. It has the potential to be developed because high economic value. The price is quite stable when compared to other food commodities. Cow manure can increase the nutrient content, the physical and chemical properties of the soil. You can also provide liquid organic fertilizer in the form of KSM to add the nutrients. KSM fertilizer is a new fertilizer circulating at the farmer level. It’s claimed to increase the absorption of fertilizer by plants. Research method used was a completely randomized block design which arranged in a factorial manner with three replications. The first factor is the dose of manure and the second factor is the frequency of fertilization of KSM to promote plant growth. Treatment without manure and KSM is as a comparison factor (control). The results showed that the dose of 1.2 kg of manure and the time of spraying every 3 days after planting could increase the growth and yield of mungbean. Dosage of manure and time of spraying don’t interact both of them.